2009
DOI: 10.1177/0310057x0903700109
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Simulation-based Team Training for Post-cardiac Surgical Emergency Chest Reopen in the Intensive Care Unit

Abstract: Emergency chest reopen of the post cardiac surgical patient in the intensive care unit is a high-stakes but infrequent procedure which requires a high-level team response and a unique skill set. We evaluated the impact on knowledge and confidence of team-based chest reopen training using a patient simulator compared with standard video-based training. We evaluated 49 medical and nursing participants before and after training using a multiple choice questions test and a questionnaire of self-reported confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…In situ simulation offers a unique form of experiential learning that has been effectively used in the labour/delivery room,6 OR suite,8 14 34 ED,16 trauma resuscitation room,7 13 17 35 PICU36 and hospital inpatient ward 9 11 12 15 37–39. In the current series, we report our experience with the use of in situ simulation to identify and resolve latent safety threats and improve the quality of care delivered to children suffering a cardiopulmonary arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In situ simulation offers a unique form of experiential learning that has been effectively used in the labour/delivery room,6 OR suite,8 14 34 ED,16 trauma resuscitation room,7 13 17 35 PICU36 and hospital inpatient ward 9 11 12 15 37–39. In the current series, we report our experience with the use of in situ simulation to identify and resolve latent safety threats and improve the quality of care delivered to children suffering a cardiopulmonary arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Donabedian,8 the framework breaks quality down into the domains of structure, process, and outcome. [11][12][13] In situ trauma simulation is an effective strategy for communication, teamwork, and technical skills training, allowing educators to control the quality and quantity and create an "on-demand" learning experience. This includes data on the system preparedness and health care team skills in the management of pediatric emergencies.…”
mentioning
confidence: 99%
“…10 Using in situ simulation to orient hospital staff to new emergency departments (EDs) is not a new concept. Studies have found that using simulation is an effective tool to identify latent safety threats, 4 increase ability to perform specific actions, 5 detect potential system and equipment issues, 11 and improve response time 8 within emergency settings. In situ simulation is believed to increase clinical learning and ultimately patient safety because it imparts an integral emotional component to the learning experience and allows learners to immediately apply what they have learned.…”
mentioning
confidence: 99%